Herbal For Anxiety In Psychology Case: Bibliometric Analysis - Shafiya, Salsabila; Mustikawati, Irma Finurina; Septianawati, Paramita; Immanuel, Glorio (Syntax Corporation Indonesia, 2024)
This research aims to carry out an in-depth analysis of the effects of herbs on anxiety in psychological cases. In order to address the complex character of anxiety disorders, there is a link between herbal therapies for anxiety in psychological cases and the integration of psychological and herbal viewpoints. Herbal treatments provide supplementary options for modifying neurobiological mechanisms underpinning symptom presentation, whereas psychological therapies focus on the cognitive, emotional, and behavioural elements of anxiety. Bibliometric analysis was done using VOSviewer software, and data was taken from the Scopus database. Data was taken by searching for keywords that were appropriate to this research, namely